Pengembangan Lembar Kerja Siswa Berbasis Project Based Learning Bermuatan Islami dalam Meningkatkan Kemampuan Pemahaman Konsep - Febi Febriyani; Yanti Mulyanti; Hamidah Suryani Lukman (Jurnal Tadris Matematika, 2018)
This study’s is the result of research that aims to develop the Student Worksheet Project Based Learning based Islamic charged in enhancing the ability of understanding the concept. The research was conducted by the Research and Development (R & D) was applied in 10 stages of research. Data collection instruments were used expert assessment form to determine the product validation, evaluation sheets and questionnaires student's teacher to determine the practicality of the product, as well as a test sheet to determine the ability of understanding the concept of product effectiveness. The results of the data analysis Student Worksheet validation assessment by experts to get an average score of 4.29 with high decent criteria. The results of the data analysis Student Worksheet practicability assessment by the teacher to get a score of 4.4 with the criteria very decent and student questionnaire on a small scale and large scale each get a score of 3.33 to 4.06 with the criterion of good and very good criteria. The results of the assessment of effectiveness of data analysis Student Worksheet tests are divided into two groups, namely small-scale test with 20 students and a large-scale test with 40 students. The results of two tests to get a score each, which is the average value of small-scale student 73.44 and an average value of large-scale student 73.75. The average value of student test small scale and large-scale use of the above KKM school is 70.